An Investigation of the Necropoleis of Kytaion and the Iluraton Plateau (2006–2013) - Khrshanovskiy, Vladimir (Hyperboreus, 2015)
A survey of the excavations of the necropoleis of Kytaion and on the Iluraton plateau conducted by the expedition of the State Museum of the History of Religion (2006–2008), the Institute for the History of Material Culture, RAS (since 2009) and the Institute of Archaeology of the Ukrainian National Academy of Sciences.